2017
DOI: 10.3390/app7010090
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Aspergillus parasiticus Infection in Maize Kernels Using Near-Infrared Hyperspectral Imaging and Multivariate Data Analysis

Abstract: Fungi infection in maize kernels is a major concern worldwide due to its toxic metabolites such as mycotoxins, thus it is necessary to develop appropriate techniques for early detection of fungi infection in maize kernels. Thirty-six sterilised maize kernels were inoculated each day with Aspergillus parasiticus from one to seven days, and then seven groups (were determined based on the incubated time. Another 36 sterilised kernels without inoculation with fungi were taken as control (DC). Hyperspectral images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…This study agrees with the findings of others that NIRS is useful for the separation of crops contaminated by aflatoxigenic strains of Aspergillus [33,43]. The separation of the milk stage from the dough and dent stage kernels observed could be attributed to the difference in path length within the grain; this is associated with presentation effects due to its smaller size [44] and difference in chemical compositional properties [38,45].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study agrees with the findings of others that NIRS is useful for the separation of crops contaminated by aflatoxigenic strains of Aspergillus [33,43]. The separation of the milk stage from the dough and dent stage kernels observed could be attributed to the difference in path length within the grain; this is associated with presentation effects due to its smaller size [44] and difference in chemical compositional properties [38,45].…”
Section: Discussionsupporting
confidence: 91%
“…This suggests important changes in this region of the spectral data ( Figure 4). These wavelength regions, as reported by others in aflatoxin contamination [26,43], are associated with changes in the macromolecules of the maize grains including starch and proteins and the fungal structures [51].…”
Section: Discussionsupporting
confidence: 65%
“…Prediction images were created to mark fungi with different incubation times in different colors. The prediction images were obtained by applying the optimal wavelengths SVM model to every pixel of the fungal hyperspectral image, respectively [17]. The prediction images of A. flavus and A. parasiticus were shown in Figure 9a,b, respectively.…”
Section: Optimal Wavelengths Svm Modelsmentioning
confidence: 99%
“…Zhao et al detected the contamination level of maize kernels inoculated with A. parasiticus by using hyperspectral images with a spectral range of 1000-2500 nm. The studies showed that hyperspectral imaging has become a promising non-destructive technique for detecting the fungal contamination levels and fungal species on cereals [17].…”
Section: Introductionmentioning
confidence: 99%
“…The training samples are used to train the DBN and the SOM; the fine tuning samples are a subset of training samples that have been manually labeled [26,27,32]. Fine tuning is used to learn the category data which is already known from the training process.…”
Section: Network Trainingmentioning
confidence: 99%